Seedling emergence, periodic growth, and survival of some multipurpose agroforestry tree species of Garhwal Himalaya - Kanchan Rawat; CS Dhanai; VP Khanduri; Bhupendra Singh (Open Journal of Environmental Biology - Peertechz Publications, 2024)
This study evaluated the seedling emergence behavior, growth performance, leaf area, and biomass allocation of seven multipurpose tree species (Celtis australis, Grewia optiva, Bauhinia retusa, Bauhinia variegata, Ficus auriculata, Quercus semecarpifolia, Quercus floribunda). The (emergence) germination experiments were conducted under the polyhouse condition in poly bags. Significant differences (p < 0.05) were found among different tree species for nursery germination percent. The seedling emergence and Seedling Vigour Index (SVI) significantly varied among all the seven multipurpose tree species. Seed germination was maximum (80%) recorded in G. optiva and minimum (21%) was recorded in Q. semecarpifolia irrespective of tree species. Significant (p < 0.05) variation was also observed for Mean Germination Time (MGT) and Germination Index (GI) among tree species. Significant variations were found in the performances of seedling growth for leaf area in periodic intervals and it is also noted that a significant difference was found in the performance of seedling growth for survival percentage at periodic intervals.